2018
DOI: 10.1002/pon.4743
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of studies exploring physical activity among adolescents and young adults diagnosed with cancer

Abstract: We can conclude that physical activity is not well researched among AYAs. More high-quality research adopting longitudinal or intervention study designs that incorporate a range of descriptive, physical, personal/psychological, social, and environmental measures are warranted to better inform the development of behavior change interventions as well as to establish the benefits of physical activity for AYAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 82 publications
(261 reference statements)
1
28
0
Order By: Relevance
“…Significant improvements were observed in some domains of physical function (lung function, fitness and flexibility). This is promising and reflective of existing data from intervention studies conducted among adolescent and childhood cancer survivors of a similar age [28,29,33,34]. The improvements in chronic fatigue scores, sleep quality and HRQoL are also encouraging and reiterate the benefit of physical activity upon the psychosocial health and well-being of young adults with cancer [35,36].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Significant improvements were observed in some domains of physical function (lung function, fitness and flexibility). This is promising and reflective of existing data from intervention studies conducted among adolescent and childhood cancer survivors of a similar age [28,29,33,34]. The improvements in chronic fatigue scores, sleep quality and HRQoL are also encouraging and reiterate the benefit of physical activity upon the psychosocial health and well-being of young adults with cancer [35,36].…”
Section: Discussionsupporting
confidence: 52%
“…Interest in programme participation was high with 98 young adults expressing interest in the 9-month recruitment window; 77% of young adults who signed up for the RENEW programme attended at least one exercise session with 61% of these young adults completing the full 12-week programme. This rate of uptake is notably higher than many exercise intervention studies conducted in the hospital setting or academic setting among similar age groups [28,29]. It is likely that the delivery of the programme by a trusted charity organisation, the ease of the referral process and the guarantee of personally tailored exercise support alongside free gym membership underpinned young adults' interest in enrolling.…”
Section: Discussionmentioning
confidence: 90%
“…This was to be expected given the strong evidence base which demonstrates physical activity is beneficial for the management of cancer-related fatigue during and after treatment [23]. Among adolescents and young adults, there is growing evidence that the same holds true [24][25][26][27]. For example, in one study of adolescent cancer survivors, exercise was found to partially mediate the relationship between fatigue and quality of life during treatment and the relationship between sleep quality and quality of life posttreatment [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, very little is known regarding the current health behaviour status of TYA cancer patients or survivors and whether their lifestyles differ to the general population. Of the few studies which have investigated the health behaviours of young people with cancer, the majority have been conducted in the USA and predominantly explored the health behaviour status of long-term survivors of a cancer diagnosed during childhood [8][9][10][11][12][13][14]. Data from these studies suggest TYA-aged cancer patients and survivors have low levels of physical activity, consume relatively poor diets, often struggle with weight gain, and engage in health-risk behaviours such as smoking and alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%